2022
DOI: 10.5851/kosfa.2022.e61
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Pre-Plating Method of Chicken Satellite Cells for Cultured Meat Production

Abstract: The treatment and use of experimental animals were approved by the Institutional Animal Care and Use Committee (IACUC) at Gyeongsang National University (approval no. GNU-210308-C0028). All step of experiments were complied with IACUC standard procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Recently, studies on adding a shaking process to increase the efficiency of pre-plating have been reported [ 29 , 46 ]. Yoshioka et al [ 29 ] isolated MuSCs from human and mouse muscles using a pre-plating method with incubation and shaking steps added (shaking the dish every 5 min 10 times).…”
Section: Musc Isolation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies on adding a shaking process to increase the efficiency of pre-plating have been reported [ 29 , 46 ]. Yoshioka et al [ 29 ] isolated MuSCs from human and mouse muscles using a pre-plating method with incubation and shaking steps added (shaking the dish every 5 min 10 times).…”
Section: Musc Isolation Methodsmentioning
confidence: 99%
“…Therefore, this maximizes the separation effect. Kim et al [ 46 ] studied the effects of shaking on the isolation of MuSCs from chickens. They analyzed the characteristics of MuSCs isolated by varying the shaking time (shaking every 8 or 15 min) and pre-plating time (1, 2, 3, and 4 h).…”
Section: Musc Isolation Methodsmentioning
confidence: 99%
“…Pre-culture is a technique for isolating specific cells from a mixture of different cell types, effectively increasing the purity of MSCs by exploiting differences in the adhesion properties of primary intracellular fibroblasts and MSCs ( Richler and Yaffe, 1970 ). The preincubation time used in the isolation of bovine MSCs reported in 2023 was 1–3 h. Fibroblasts begin to adhere 5 min after incubation and adhere to surfaces faster than MSCs, indicating that a relatively high purity of Pax7- or MyoD-positive cells can be obtained using the preincubation process ( Table 3 ; Kim et al, 2022 ; Xu et al, 2018 ; Yoshioka et al, 2020 ). In other studies, preincubation conditions have been shown to vary from 5 min to 24 h after fibroblasts begin to adhere ( Table 3 ).…”
Section: Recent Trends In Muscle Satellite Cell Culture Technologiesmentioning
confidence: 99%
“…One of the effective methods for rat MSCs was preincubation for up to 10 min with shaking every 5 min ( Yoshioka et al, 2020 ). For chicken MSCs, it was up to 2 h with shaking every 8 min after 2 h of rest, indicating that the preincubation conditions may also vary depending on species-specific cell characteristics ( Kim et al, 2022 ).…”
Section: Recent Trends In Muscle Satellite Cell Culture Technologiesmentioning
confidence: 99%
“…FACS utilizes antigen–antibody reactions to recognize surface markers on cells as antigens, which have been pre-labeled with fluorescent substances to facilitate the cell sorting process. A flow cytometer is used to separate the cells, allowing for the precise analysis of their size and internal structure ( Kim et al, 2022b ). Furthermore, the integration of FACS with sequencing, known as FACSeq, proves to be highly effective.…”
Section: Manufacturing Of Cultured Meatmentioning
confidence: 99%